Analisis Hukum Perdata Internasional dalam Penyelesaian Sengketa Pernikahan yang Dilaksanakan di Luar Negeri - Ratna Kumala, Berta; Rafi, Kamaludin; Tegar Rizky SP, Muh; Radiansyah, Muhammad Yuflih Ksatria; Mul Erowati, Eti (UNIVERSITAS SERAMBI MEKKAH, 2025)
Cross-border marriages are increasingly common in the era of globalization, but this also creates legal complexities in settling marriages. Private international law plays an important role in regulating legal relations involving foreign elements. This research aims to analyze various aspects of international civil law that are relevant in the settlement of marriage trials carried out abroad. The research method used is a normative juridical approach, by collecting primary data through interviews and secondary data from the literature. The research results show that differences in legal systems between the couple's country of origin and the country where the marriage took place can create complexity in resolving disputes. The application of private international law principles, such as acquisition, choice of law, and recognition and enforcement of foreign judgments, can help reduce conflicts that occur and ensure justice and legal certainty.